Re-description of Orchestia stephenseni Cecchini, 1928: designation of neotype and senior synonym to Orchestia constricta A. Costa, 1853 (Crustacea: Amphipoda: Talitridae) by Reversal of Precedence - Iaciofano, Davide; Brutto, Sabrina Lo (Zootaxa, 2016)
The beach flea Orchestia stephenseni was originally described by Cecchini (1928), and successively by Karaman (1973). The description of this species will be herein revised by focusing on the variation of the gnathopod 2 in males, as detected during its growth period. An analysis of DNA Barcoding was performed to support the assignment of the taxonomic species to five morphotypes. As the type specimen has not yet been designated, a neotype is assigned. The name of the species is here presented as a valid name as it satisfies the requirements of a Reversal of the Principle of Priority: Orchestia stephenseni takes precedence over the objective synonym Orchestia constricta A. Costa, 1853, in accordance with Article 23.9.2. of the International Code of Zoological Nomenclature. Orchestia stephenseni Cecchini, 1928 becomes nomen protectum, and Orchestia constricta nomen oblitum. The results presented in this paper also support the status of Orchestia stephenseni as a Mediterranean endemic species, thereby rejecting previous Atlantic records. The synonymies for O. stephenseni are revised accordingly.